Dante and the Arthurian Literature: Contexts, Reception and Critical Perspectives - Caccialupi, Gianluca (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of Italian, 2024)
This doctoral dissertation offers the first comprehensive study of Dante¿s reception of Arthurian literature. In particular, it aims to identify the Arthurian romances that Dante knew, to define the ways in which he read them, and to show how the study of these sources in relation to his wider literary production helps to shed light on some important aspects of the Commedia. To achieve these aims, I begin with an overview of the circulation of the Matter of Britain in thirteenth and early fourteenth-century Italy. Drawing on recent scholarship on the subject, I show how Arthurian literature, and the prose romances in particular, enjoyed great popularity among thirteenth and early fourteenth-century Italian translators and poets. Most of them looked to the stories of Tristan and Lancelot for examples of political and civic virtue, as well as for ideal models of courtly love. I then show how Dante¿s reception of Arthurian literature is highly original in comparison with previous Italian authors. In particular, he focuses on moral themes, contrasting Tristan¿s death in a sinful state, which led to his damnation, with the conversion of Lancelot, who overcomes his adulterous relationship with Guinevere and consecrates himself to God at the end of the Lancelot en prose. The similarities between the stories of Lancelot and Dante are evident in the cantos in which the poet reflects on his sinful past, and show how Arthurian literature may have played a role in the depiction of Dante¿s journey to redemption as presented in the Commedia.
APPROVED
Keywords: Arthurian Literature; Lancelot-Graal; Tristan; Italian Studies; Medieval Studies; Old French; Dante